52.8k views
2 votes
K(x)=1/3(x+9) and k(x)=-4, so x=?

User Zay Nields
by
5.9k points

2 Answers

0 votes

Answer:

x = -21

Explanation:

if k(x) = -4 you can substitute that into the original equation:

-4=1/3(x+9)

multiply both sides of the equation by 3

-12=x+9

subtract 9 from each side

-21=x

User Lee Oades
by
5.7k points
0 votes

Answer:

x = -21

Explanation:

k(x)=1/3(x+9) and k(x)=-4

Set them equal

1/3(x+9) =-4

Multiply each side by 3

3*1/3(x+9) =-4*3

x+9 = -12

Subtract 9 from each side

x+9-9 = -12-9

x = -21

User Lightning
by
5.7k points